Factors associated with HIV affected clients’ behavioral practices and health outcomes - Musengya, Judith; Muindi, Serah (Machakos University, 2019)
A three year cohort study in Machakos County captured the behavioural practices of HIV affected clients undergoing treatment at Comprehensive Care Centres in Machakos and Athi-River hospitals. Selection of 131 HIV infected persons was done on first come basis and interviews conducted after signed informed consent. Thirteen categories of treatment choices were exhibited by HIV infected clients. The HIV treatment using herbs, prayers and tethered Nutrition, ARVs and Septrin, social support and laboratory testing was studied alongside others e.g Micronutrient bioavailability, biodiversity and health outcomes. Tethered group exhibited a 45% improvement in ARV adherence, and a corresponding 45 % of the HIV infected Clients improving to a viral load of non detectable level. Some 14 of 131(10.7%) were still awaiting their viral load results. There was a (8 of 131) 6.1% using multivitamins formulations to boost their appetite. A group optimizing on the recommended diet biodiversity were 59 of 131 (40.04%) and 9 of 131(6.9%) eating nine+ foods daily. The basis for micro-nutrients and functional Biochemical reactions integrated and tethered on dependent factors leads to restoration to normal of biochemical metabolic reactions in the body thus cure for HIV infected person as the ARVs destroy the HIV virus. The Syndemics interplay of external environment, micro-nutrients, adhered diets and Metabolism as well as tethered targeted epidemiological interventions resulted to a tethering therapy procedure improving the health of HIV infected persons. This paper presents a paradigm shift for establishment of tethered social and spiritual support as well as counselling, tethered ARV adherence, micro-nutrient biodiversity and bioavailability and Nutritional supply.
Keywords: Tethered; Behavioural; Syndemics; Nutrition; Bioavailability; Biodiversity